De l’Esthétisation à l’anti-symbolisme : les évolutions du corps chez William Carlos Williams - Samantha Lemeunier (Sillages Critiques)
At the beginning of his career, Williams often resorts to horticultural metaphors to represent the body. However, from the 1920s onwards, his anatomical descriptions gradually lose their symbolism. After the end of the 1930s, the body is finally represented in all its nakedness without being ornamented. This paper describes this poetic undressing and analyzes the passage from a canonical body inspired from Romantic ideals to the fragile and vulnerable body that Williams depicts at the end of his career. If the 1910s constitute a period of stylistic experimentation for Williams as he draws inspiration from Whitmanian or Keatsian poems, his bodily representations emancipate from such aesthetic norms after the 1920s while the human anatomy is less associated with nature than with artificiality. This subversion of physical canons marks the singularity of the williamsian style while contaminating the textual body as the poet notably reworks various poetic genres such as the sonnet. Nevertheless, at the end of the 1930s, the body is re-naturalized as Williams witnesses the physical degradation of his dying mother; he thus represents the vulnerability of the body in his poems, the textual body freezing in time the fleeting evolutions of the physical body. Therefore, the passage from aestheticized to anti-symbolic bodies in Williams’ work is based on both the stylistic and biographical evolutions of the author, making his writing the mirror of the living and evolving bodies of his period.